Prevalence and Correlates of Vaginal Estrogenization in Postmenopausal Women in the United States - Lindau, Stacy Tessler (Menopause, 2017)
OBJECTIVE: Establish current population-based vaginal estrogenization norms for postmenopausal U.S. women. METHODS: Using a U.S. national probability sample of 868 postmenopausal women ages 57 to 85 years (mean age 67.6±0.3 years; 21.6±0.5 years since menopause), we calculated the epithelial Maturation Value generated from self–collected vaginal specimens and compared findings with historical clinical data. Linear and logistic regression were used to describe the relationship between vaginal estrogenization and sociodemographic, physical, gynecological and sexual characteristics. RESULTS: Among postmenopausal women, mean Maturation Value was 46.6±0.8 (SD 17.4, range 2.5–100) and stable across age groups. In every age group, vaginal estrogenization was higher among postmenopausal non-users of hormone therapy in the 2005–06 US cohort than reported for the 1960s Canadian clinical cohort. Maturation Value was also higher among women who used menopausal hormone therapy in the prior 12 months compared to those who did not (55.1±1.2 vs. 44.4±0.9, p<0.001). In multivariate analyses, hormone therapy use, obesity and African American race were each independently associated with higher Maturation Value. Overall, Maturation Value was not associated with sexual activity, but low Maturation Value was associated with vaginal dryness during intercourse among sexually active women. CONCLUSIONS: Compared to 1960s clinical data, current population estimates revealed higher vaginal estrogenization across all age groups and no decline with age. The strongest independent correlates of vaginal estrogenization in postmenopausal U.S. women were current hormone therapy use, obesity, and African American race. Post-menopause, half of all women exhibit low vaginal estrogenization.